Potato field-inoculation in Ecuador with Rhizophagus irregularis: no impact on growth performance and associated arbuscular mycorrhizal fungal communities - Lojan, P.; Senes-Guerrero, C.; Suarez, J.P.; Kromann, P.; Schubler, A.; Declerck, S. (Springer, 2017)
A field trial was conducted in two localities of the Ecuadorian Andes to evaluate potato (Solanum tuberosum c.v. INIAP - Fripapa) response to inoculation with four commercial products containing the arbuscular mycorrhizal fungus (AMF) strain Rhizophagus irregularis DAOM 197198. In parallel, potato roots were analysed using 454 GS-FLX+ sequencing of c. 800 bp of the nuclear LSU rRNA gene to assess the associated AMF communities. To evaluate inoculation success, sequence reads of R. irregularis on the root samples were compared between inoculated and not inoculated plants by analysing the frequency of occurrence (FO) and relative read abundance (RA). None of the commercial products significantly increased potato yield. Instead, the AMF communities were dominated by an unknown Acaulospora sp. (Sp14) found at high FO and RA in both localities. Rhizophagus irregularis was found in most of the roots of both inoculated and not inoculated plants at both localities. However, its abundance was unexpectedly low indicating poor inoculum establishment. Clearly, many factors have to be taken in consideration for the successful application of AMF-based inoculants. For the Ecuadorian field trials, several causes may explain the lack or poor establishment of R. irregularis such as inoculation technique, agricultural practices, biotic and abiotic conditions and competition with native AMF species.